Intention to adopt environmental management practices among food manufacturing SMEs in Malaysia - Latip, Malisah (2019)
Awareness on environmental and sustainable issues is globally increasing and it has been seen that existing environmental development designs cannot be sustained in the long period. Given that 98.5% of businesses in Malaysia are represented by SMEs, their impact toward environmental degradation should not be ignored. With increasing concern on environmental issues, there has been a rising demand for environmentally sound business practices among SMEs. Even though there is a growing awareness of the environmental impact caused by SMEs, this awareness is not translated into actual behaviour. SMEs consider themselves as too small to cause big impact on the environment. This can be seen from the low adoption rate of environmental certification among SMEs in Malaysia. Thus, this study endeavours to determine the factors influencing SMEs intention to adopt environmental management practices (EMPs) by focusing on food manufacturing SMEs. The conceptual framework was developed by integrating eight factors derived from two theories; (1) Technological- Organizational-Environmental (TOE) framework; and (2) Diffusion of Innovation (DOI) theory. The conceptual model was divided into three main contexts, namely; technological context consisting (i) relative advantage, (ii) complexity and (iii) compatibility; organizational context, which contains of (iv) organizational support and (v) quality of human resources; and environmental context, which encompasses (vi) customer pressure, (vii) regulatory pressure and (viii) government support. Owner manager’s attitude was included in the model as the mediating variable, whereas, firm age and firm size were employed as the moderating variables. This study used criterion sampling technique to choose the target respondents. Data were collected via email based questionnaire survey sent to 1,165 owner-managers of food manufacturing SMEs and 367 usable samples were analysed. Structural equation modeling (SEM) analysis was performed to analyse the causal effects of the determinant factors on the intention to adopt EMPs. Among eight factors tested in the structural model, six factors showed statistically significant effects on the intention to adopt EMPs with compatibility being the strongest factor, while complexity turned out to be the least important factor in the whole structural model. On the other hand, quality of human resources and customer pressure appeared to be insignificant factors. Owner-manager’s attitudes have partial mediation effects in the relationships of four variables namely relative advantage, compatibility, organizational support and regulatory pressure towards the intention to adopt EMPs. This study also provides the evidence of moderating effect of firm age and firm size on several paths in the model. Results obtained suggest that the SMEs owner managers in Malaysia have an intention to implement EMPs in their organizations. Therefore, commitment from pertinent parties such as the government and related agencies in promoting EMPs are vital in realising EMPs adoption. The government can design various strategies and instruments as part of a policy to foster environmental compliance and environmental business practices. These include introducing sector specific certifications and eco-labels, regulatory incentives, free consultation services, low-interest loans, grants, and tax rebates.